2018
DOI: 10.1093/ndt/gfy367
|View full text |Cite
|
Sign up to set email alerts
|

MAGE genes in the kidney: identification of MAGED2 as upregulated during kidney injury and in stressed tubular cells

Abstract: Abstract Background Mutations in Melanoma Antigen-encoding Gene D2 (MAGED2) promote tubular dysfunction, suggesting that MAGE proteins may play a role in kidney pathophysiology. We have characterized the expression and regulation of MAGE genes in normal kidneys and during kidney disease. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In contrast, in Clock-mutant mice, Atp1b1 expression was low and blood pressure high [44]. The expression of both NCC and ATP1B1 is altered in kidney injury, potentially linking kidney injury to an altered expression of kidney circadian genes regulating blood pressure [45,46].…”
Section: Chronodisruption In Ckdmentioning
confidence: 96%
“…In contrast, in Clock-mutant mice, Atp1b1 expression was low and blood pressure high [44]. The expression of both NCC and ATP1B1 is altered in kidney injury, potentially linking kidney injury to an altered expression of kidney circadian genes regulating blood pressure [45,46].…”
Section: Chronodisruption In Ckdmentioning
confidence: 96%
“…PGC-1α is encoded by the PPARGC1A gene and belongs to the PGC-1 family, also composed of PGC-1β (encoded by PPARGC1B), which contributes to maintain basal mitochondrial function, and PRC (PGC-1-related coactivator, encoded by PPRC1), which appears to be restricted to regulating mitochondrial biogenesis in proliferating cells [24] ( Figure 1A). While there is abundant literature on PGC-1α and kidney disease, as discussed below, much less is known about the role of PGC-1β and PRC in kidney disease, despite the fact that transcriptomic studies have identified them as differentially expressed during experimental AKI [25][26][27] (Figure 1B). [28].…”
Section: Pgc-1α: a Regulator Of Mitochondrial Biogenesismentioning
confidence: 99%
“…Once TNFRSF12a/Fn14 was identified among the highest expressed TNFRSF genes in podocytes in vivo and the most upregulated in glomeruli in human MN, the impact of its ligand TWEAK on podocyte PLA2R expression was explored in mice and in cultured human podocytes and the impact of tacrolimus on TWEAK-induced PLA2R expression was explored in cultured human podocytes. Additionally, we queried a previously published in-house database that had evaluated by transcriptomics arrays the impact of 100 ng/mL TWEAK on gene expression in murine cultured proximal tubular epithelial MCT cells [18,19]. Specifically, we queried this database for the impact of TWEAK on the expression of genes identified by GWAS to be associated with MN [16].…”
Section: Data Mining and Overall Experimental Designmentioning
confidence: 99%